UPAYA MEMBANGUN KARAKTER SISWA MELALUI INTEGRASI KONSEP HIMPUNAN DAN AL-QUR’AN DALAM PEMBELAJARAN MATEMATIKA - Izzati Rahmi HG; Admi Nazra; Budi Rudianto; Mahdhivan Syafwan; Ferra Yanuar; Hazmira Yozza; Narwen Narwen; Monika Rianti Helmi; Maiyastri Maiyastri (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The Quran is the source of all knowledge, including mathematics. On the other hand, mathematics is closely related to everyday life and the development of other fields of knowledge. Mathematics is one of the disciplines closely connected to the verses of the Quran. Mathematics education is expected to improve to meet the advancements in time and technology continually. It is also anticipated that mathematics education can build the character of each student through religious values. This activity aims to introduce the concept of sets integrated with the content of verses found in the Quran. The activity was conducted as an online Zoom meeting and YouTube streaming seminar. Participants included mathematics lecturers, teachers, and students from Islamic junior and senior high schools from ten provinces in Indonesia. The event was titled "The Quran and Set Theory" and received high appreciation from the seminar participants. This was evident from the enthusiastic participation and numerous questions raised during the Q&A session. This activity has motivated teachers and lecturers to integrate the mathematical concepts learned with the Quranic verses. Teachers who participated in this activity are expected to act as agents in popularizing the method of integrated mathematics education with the content of Quranic verses, especially set theory.